Adventures of a cat-whiskered girl - Pinkwater, Daniel Manus, 1941- (Houghton Mifflin Books for Children, 2010)
Big Audrey, who has cat-like whiskers, and her telepathic friend Molly set out on a journey to find out why flying saucers are landing behind the old stone barn in Poughkeepsie, New York, and, more importantly, to determine whether another cat-whiskered girl really exists.